THE ANALYSIS OF STUDENTS’ LEARNING STYLE - Isnaeni Wahab; Nuraeni Nuraeni (SELTICS, 2020)
The aim of this research is to find out the types of learning style which students have. The population in this study was the students of English Department in academic year 2017 which amounted to 24 students. The research was conducted at Muslim University of Maros (UMMA), South Sulawesi. This research was a qualitative descriptive research. In collecting the data, the researcher used questionnaires and documents. The questionnaires in this research were used to determine what learning styles were dominated by students in the learning process. The results of the learning style analysis of the students showed that there are 12 (50%) students were categorized as visual learners, 8 (33%) students were categorized as auditory learner, and 4 (16%) students were categorized as visual-auditory learners.